Sgraffito pottery in the Ottoman Timisoara “Palanca Mare” suburb: ICAM excavation point (2015 Campaign) - Gaşpar, Adriana (Journal of Islamic Archaeology, 2019)
Rescue excavations conducted at ICAM in Timisoara have shed light on a relatively rare pottery type of the Ottoman period. Since the 2015 campaign, great strides have been made in Ottoman period archaeology in Timisoara, but little attention has been given to the everyday ceramics of the site. The sgraffito pottery from Timisoara represents a distinctive indicator of the mentality and consumption habits of the communities of the Ottoman period. Analysis of this pottery type has shed light on the nature of the various social and economic networks that developed under Ottoman rule. Deriving the multifaceted meanings attached to these sgraffito wares will contribute to the overall history of Timisoara during the Ottoman era (16th–17th centuries), and within the context of other archaeological remains it will aid in reconstructing the topographical situation of the town and its social life.Click to view Figures